Flexural behavior of composite T-beam made of plastic waste aggregate concrete web and high-strength concrete flange. (January 2023) - Faqe Rahim, Aso A.; Mohammed, Azad A.; Al-Kamaki, Yaman S.S.
Abstract: The growth of post-consumed plastic waste needs recycling for new products. One of the methods of recycling is the use of plastic waste in concrete in the form of shredded aggregate and plastic fibers. Researches on the performance of structural members made of plastic waste recycled concrete are limited. In this study, a novel composite T -section beam made of high-strength concrete (HSC) for flange and plastic waste aggregate concrete (PWAC) for the web is investigated. Firstly, tests on materials were performed to measure compressive strength, tensile strength, shear transfer between the two concretes, and steel pull-out strength for the two concretes. Later, design of a composite T -beam was made for flexure, shear force, and shear connection between the flange and the web of the section. Results show that when PWAC is used to surround steel rebar, it affects the interfacial bond, and the steel will not yield. However, the first crack load will be high compared with the beams of tension steel surrounded by HSC . The design of shear connectors could be successful for the composite section using the ACI -PCI design procedure. Six composite T- beams were designed and tested. The mode of failure was found to be pure flexure and the test ultimate load capacity was found to be higher than the calculated one by a ratio between 1.295 and 2.212.